Real-time estimation of transmission line impedance based on modal analysis theory - Asti, G. A. [UNESP]; Kurokawa, S. [UNESP]; Costa, E. C M; Pissolato, J. (Institute of Electrical and Electronics Engineers (IEEE), 2011)
The objective of this paper is to show a methodology to estimate the longitudinal parameters of transmission lines. The method is based on the modal analysis theory and developed from the currents and voltages measured at the sending and receiving ends of the line. Another proposal is to estimate the line impedance in function of the real-time load apparent power and power factor. The procedure is applied for a non-transposed 440 kV three-phase line. © 2011 IEEE.
Keywords: Parameters estimation; Transmission line modeling; Transmission lines; Analysis theory; Apparent power; Currents and voltages; Line impedance; Power factors; Real-time estimation; Three-phase lines; Transmission line; Transmission line impedance; Electric lines; Electric power factor; Electric utilities; Estimation; Modal analysis; Transmission line theory